A COMPARATIVE STUDY ON NASAL BONE FRACTURE ASSOCIATED WITH SEPTAL DEVIATION CORRECTED WITH SEPTOPLASTY VERSUS CLOSED REDUCTION - SREENIVASAN, SREEJITH (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The dorsum of the nose formed by nasal bones helps to maintain the airway and esthetic appearance of the nose. Faciomaxillary trauma is associated with a nasal bone fracture with or without nasal septal fractures. Nasal bone fractures can lead to deviation of the external nose and nasal obstruction. The management includes correction of nasal bone deformity with either septoplasty or reduction of nasal septal deviation by the non-surgical method. A study was conducted to compare the results of septal deviation corrected by septoplasty and non-surgical reduction of septal deviation combined with nasal bone fracture reduction.The aim of this study was to compare the results of septal deviation corrected by septoplasty and non-surgical reduction of septal deviation combined with nasal bone fracture reduction. Materials: Sixty-two patients with nasal bone fractures with varying degrees of external nose deformity and nasal septal deviation were divided into two groups. Group A consisted of patients treated with septoplasty and nasal bone fracture correction and Group B consisted of patients treated with non-surgical reduction of septal deviation and nasal bone fracture correction. Type I, II, and II nasal bone fractures were included with all types of septal deviations. The subjective improvement in nasal obstruction was assessed using the visual analog scale in both groups. Results: There were 26 males (81.25%) and 06 (18.75%) females in Group A and 25 (83.33%) males and 05 (16.67%) females in Group B. In Group A, 12 (37.5%) patients were aged between 18 and 27 years, 10 (31.25%) patients were aged between 28 and 27 years, 07 (21.87%) patients were aged between 38 and 47 years, and 03 (09.37%) patients were aged between 48 and 57 years. The mean age was 23.54±2.30 years. Conclusion: Nasal bone fractures cause not only esthetic facial deformity but also functional airway obstruction. A thorough clinical examination, computed tomography scan, and patient counseling are necessary. There is no statistically significant difference in the final outcome between the septoplasty and closed reduction of the septal deviation undertaken to relieve nasal obstruction in patients with associated nasal bone fractures.